PENGARUH JARAK KE SEKOLAH TERHADAP ANGKA PARTISPASI DAN PUTUS SEKOLAH SMP DI INDONESIA - Robby A Sirait (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2019)
This research empirically to analyze the effect of distance to school on junior secondary enrolment rate and schools dropout rate in Indonesia. The data were collected from 33 provinces between 2010 and 2017. To analyze cross-provinces panel data, we used fixed effect model (FEM). The findings showed a positive relationship between distance to school and schools dropout rate. But, the relationship not statistically significant. Another finding is the distance to school have a negative influence on enrollment rate and statistically significant. And finally, we provide a few recommendations which policy makers may adopt in reducing dropout from school and increasing enrollment rate of junior secondary school.